The Role of Civic Engagement and E-Government in Enhancing Accountability and Transparency in Metropolitan City Management - Prakosos, Riyan Dwi Yulian; Suherlan (ADMAN: Journal of Contemporary Administration and Management, 2025)
This study aims to analyze the role of civic engagement and e-government in improving accountability and transparency in metropolitan city management. The method employed is a literature review with a qualitative approach and descriptive analysis. Data were collected from Google Scholar and other credible and relevant websites, covering publications from 1989–2025. From an initial pool of 40 articles, a rigorous selection process based on relevance, methodological quality, and source credibility yielded 31 articles for further analysis. The findings indicate that civic engagement serves as a participatory mechanism that strengthens the legitimacy of public policies, while e-government functions as a digital infrastructure that expands information access, accelerates communication, and facilitates real-time public oversight. The integration of these two elements has been shown to enhance metropolitan governance accountability and transparency, supported by the Participatory Governance Theory, Technology Acceptance Model, Accountability Theory, and Transparency Theory. Case studies in Jakarta, Surabaya, Seoul, and New York confirm that successful implementation depends heavily on inclusive system design, public digital literacy, and the government’s commitment to openness. This research offers a theoretical contribution to the development of smart governance concepts and provides practical implications for urban policymakers seeking to establish governance that is responsive, open, and trustworthy.